UJI TOLERANSI BEBERAPA VARIETAS PADI (Oryz - Halimatussakdiah Halimatussakdiah; Luthfi A. M. Siregar (Jurnal Agroekoteknologi, 2013)
The objective of this study is to have a reliable variety to extend on an used cultivated land. Thisresearch was carried out on an used cultivated land as fish pond with salty sulfate contained onKecamatan Percut Sei Tuan in a height site ± 2 m asl with its coastal far distance ± 1 km, has DHL6.5 - 6.8 and pH 4.1 – 4.6. The research adopted group random design with 18 varieties of rice asplant to test. The parameter to analyze such as height of plant, number of saplings, number ofproductive saplings, length of grains, numbers of grains, number of decomposed grains, grainsproduction and wet weight and dried weight of roots.The result of research indicated amongst different of varieties as tested showed a significantdifferent on all parameter as analyzed. Out of 18 varieties that has been tested were found 12varieties survivable, whereas the varieties prospective to extend on the used cultivated land locationwith salty sulfate such as Banyuasin, Dendang, Siak Raya, Punggur and Lambur regions.Keywords : tolerated test, rice, salty sulfate